2016
DOI: 10.1007/s10396-016-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastographic evaluation of the median nerve in hemodialysis with carpal tunnel syndrome

Abstract: Sonoelastography helps to improve the diagnostic accuracy of the ultrasonographic assessment of CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…The MN-CSA was not correlated with the dialysis vintage, a result that is in contrast to other previously published studies, which suggested the duration of dialysis treatment to be a significant risk factor for the development of CTS [5,13,35]. This difference can be explained by the relatively shorter duration of dialysis treatment in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The MN-CSA was not correlated with the dialysis vintage, a result that is in contrast to other previously published studies, which suggested the duration of dialysis treatment to be a significant risk factor for the development of CTS [5,13,35]. This difference can be explained by the relatively shorter duration of dialysis treatment in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Using clinical manifestations plus positive Tinel's test as the reference standard, MN-CSA with a threshold of 11.5 mm 2 can indicate the probability of CTS with 63% sensitivity and 80% specificity. This is consistent with a previous study carried out on 71 HD patients (22 with and 49 without CTS), which identified the cutoff value of the MN-CSA for detection of CTS as 11 mm 2 with 79.2% sensitivity and 84% specificity [13]. About one-third of this cohort had MN-CSA ≥ 11.5 mm 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several new sonographic techniques, such as dynamic US and US elastography, have been developed in recent years and have the potential to differentiate CTS of different severities. 10 12 However, the ultrasonic morphology of the carpal tunnel, including the anatomy of the median nerve, may vary according to ethnicity, sex, and age. 13 , 14 Cut-off values specific to different ethnic groups would be of great benefit for practicing clinicians and radiologists.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have described the potential of elastography for CTS, with the majority reporting increased nerve stiffness (ratios) in patients with CTS 20–32 ; three research studies reported no significant difference 33–35 . In addition, US elastography has been used to assess carpal ligament stiffness, 36,37 intra carpal tunnel pressure, 38,39 the correlation between median nerve area and strain 40 and the difference in median nerve elasticity before and after carpal tunnel release 41 .…”
Section: Introductionmentioning
confidence: 99%